2010
DOI: 10.4061/2010/838917
|View full text |Cite
|
Sign up to set email alerts
|

Placental Vascular Obstructive Lesions: Risk Factor for Developing Necrotizing Enterocolitis

Abstract: Necrotizing enterocolitis (NEC) is a severe neonatal disease affecting particularly preterm infants. Its exact pathogenesis still remains unknown. In this study, we have compared the prevalence of vascular obstructive lesions in placentae of premature newborns which developed NEC and of a control group. We further compared separately the findings of placentae of infants of less than 30 weeks of gestation, the age group in which NEC occurs most frequently. We found signs of fetal vascular obstructive lesions in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…In addition, some studies have identified a relationship between NEC and fetal thrombotic vasculopathy or fetal vascular obstructive lesions [4; 48]. In our study, fetal large vessel thrombi were significantly associated with an increased risk of NEC and trended with an increased risk of ROP and BPD.…”
Section: Discussionsupporting
confidence: 65%
“…In addition, some studies have identified a relationship between NEC and fetal thrombotic vasculopathy or fetal vascular obstructive lesions [4; 48]. In our study, fetal large vessel thrombi were significantly associated with an increased risk of NEC and trended with an increased risk of ROP and BPD.…”
Section: Discussionsupporting
confidence: 65%
“…The etiology of NEC is still poorly understood, but it is believed to be multifactorial [87]. Several studies found an association between NEC and placental lesions, in particular fetal vascular obstructive lesions (fetal thrombotic vasculopathy, congested villi, coagulation-related lesions) with ORs ranging from 2.6 to 9.10 (95% CI: 1.13–15.08) [26], [32], [33]. The presence of ischemia has been proposed as an explanation for the etiology of NEC.…”
Section: Resultsmentioning
confidence: 99%
“…As described above, high grade FVM (fetal thrombotic vasculopathy) has the highest rate of associated adverse outcomes, particularly CNS abnormalities (cerebral palsy, neonatal encephalopathy, perinatal stroke, intracranial hemorrhage) . Less well established associations with placental FVM include maternal diabetes and a variety of fetal/neonatal abnormalities including necrotizing enterocolitis, congenital leukemia, neonatal alloimmune thrombocytopenia, gastroschisis, and non‐cardiac congenital malformations .…”
Section: Clinical Correlationsmentioning
confidence: 99%